2016
DOI: 10.1016/j.anorl.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Receptive speech in early implanted children later diagnosed with autism

Abstract: Preoperative psychological assessment in congenitally deaf infants should be expanded by the use of validated instruments for early detection of autism. The possibility of developing ASD should be kept in mind by all professionals involved in programs for cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 23 publications
1
21
0
7
Order By: Relevance
“…All seven articles were analyzed according to the JBI 14 according to each type of study: JBI Critical Appraisal Checklist for Cohort Studies ( Table 2 ), JBI Critical Appraisal Checklist for Studies Reporting Prevalence Data ( Table 3 ), and JBI Critical Appraisal Checklist for Case Report ( Table 4 ). Four articles 11 , 20 , 21 , 22 showed a low risk of bias, and three article 19 , 23 , 24 showed a moderated risk of bias.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…All seven articles were analyzed according to the JBI 14 according to each type of study: JBI Critical Appraisal Checklist for Cohort Studies ( Table 2 ), JBI Critical Appraisal Checklist for Studies Reporting Prevalence Data ( Table 3 ), and JBI Critical Appraisal Checklist for Case Report ( Table 4 ). Four articles 11 , 20 , 21 , 22 showed a low risk of bias, and three article 19 , 23 , 24 showed a moderated risk of bias.…”
Section: Resultsmentioning
confidence: 93%
“…Four articles were excluded in this stage for the following reasons: two articles 15 , 16 showed the absence of a subject with ASD + CI; two 17 , 18 did not present pre- and postoperative data of the subjects, present the mother’s perception, and do not show auditory or communication aspects. Seven studies 11 , 19 , 20 , 21 , 22 , 23 , 24 were selected for qualitative analysis in the present SR ( Table 1 ). No studies were found by performing a manual search of the references of the articles.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, most children with ASD do have gains in speech perception and expression post CI. It was also found that continued improvement could occur for several years (38,40). It must be noted that the above refers to any improvement and not necessarily a meaningful improvement in speech perception and expression.…”
Section: Discussionmentioning
confidence: 95%
“…There were five studies that compared outcomes of children with ASD and typically developing children (21,26,33,40). As noted earlier, normally developing children were on average implanted earlier and were bilaterally implanted more frequently.…”
Section: E4 R Mathew Et Almentioning
confidence: 99%
“…Some authors suggest that in such cases, the most common is profound sensorineural hearing loss (9) . Numerous researchers also pay attention to significant difficulties in the development of speech in deaf children supplied with cochlear implants who have been diagnosed with autism (10)(11)(12) . In the school and preschool period, conductive and mixed hearing loss are often a problem, which often goes unnoticed even in healthy children.…”
mentioning
confidence: 99%